1987
DOI: 10.1038/329056a0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid removal of Chernobyl fallout from Mediterranean surface waters by biological activity

Abstract: The sinking of particulate organic matter from the euphotic zone is an important pathway for the vertical transport of many elements and organic compounds in the sea. Many natural and artificial radionuclides in surface waters are readily adsorbed onto suspended particles and are presumably scavenged and removed to depth on time scales commensurate with both particle sinking rate and retention time of the radionuclide on the particle. Previously, abyssal benthic organisms from the northeast Pacific were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(76 citation statements)
references
References 21 publications
5
69
1
1
Order By: Relevance
“…Zooplankton activity and the incorporation of mineral particles into faecal pellets have also been proposed as a mechanism to explain such lithogenic events (e.g. Fowler et al 1987;BuatMenard et al 1989). Ternon et al also found another 'lithogenic event', in summer when the surface mixed layer is depleted in nutrients, where only 20 % of the POC exported could be explained by fixation of carbon induced by atmospheric fertilisation, the rest being assumed to be due to the incorporation of mineral particles acting as ballast in organic aggregates formed by the dissolved and colloidal organic matter present in the water column prior to the event.…”
Section: Particulate Matter and Carbon Exportmentioning
confidence: 99%
“…Zooplankton activity and the incorporation of mineral particles into faecal pellets have also been proposed as a mechanism to explain such lithogenic events (e.g. Fowler et al 1987;BuatMenard et al 1989). Ternon et al also found another 'lithogenic event', in summer when the surface mixed layer is depleted in nutrients, where only 20 % of the POC exported could be explained by fixation of carbon induced by atmospheric fertilisation, the rest being assumed to be due to the incorporation of mineral particles acting as ballast in organic aggregates formed by the dissolved and colloidal organic matter present in the water column prior to the event.…”
Section: Particulate Matter and Carbon Exportmentioning
confidence: 99%
“…The latter appears in contrast with the now emerging viewpoint of rapid (reductive) mobilization of natural (stable) Ce under reducing conditions (this and aforementioned papers). The fate of REE radioisotopes arising from Chernobyl fallout in both oxygenated waters (FOWLER et al, 1987) as well as the anoxic Black Sea (BUESSELER et al, 1987;BUESSELER et al, 1990) has important implications for our study, and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…The other part will generate, after dying, large aggregated particles, known collectively as marine snow, which can reach the deep waters (Asper et al, 1992) and thus contribute to the contamination of sediment and benthic organisms, especially in the coastal area. This phenomenon was observed in the Mediterranean Sea a few days after the Chernobyl accident, generating a rapid transport of some radionuclides from surface waters to a depth of 200 m (Fowler et al, 1987). This process could be expected in the Japanese coastal area characterized by very high levels of contamination, especially around FNPP.…”
Section: Belharet Et Al: Ecosystem Model-based Approach For Modelmentioning
confidence: 97%